Pengaruh Konversi Lahan terhadap Livelihood Asset dan Strategi Nafkah Rumah Tangga Buruh Tani - Tuti Artianingsih; Heru Purandar (JURNAL KAJIAN ISLAM MODERN, 2019)
Land conversion is land use change from agricultural (sector) to non-agricultural (sector). The land conversion that occurred in the Cimanggu Satu village caused work patterns to change, revenue levels to change, undertaken land area changes, and income changes. The impact of land conversion will affect the livelihood strategies that adopt attitudes. Livelihood strategies are applied by hodge households not only in the agricultural sector but also in the non-agricultural sector. The application of livelihood strategies was carried out on the engineering of agricultural livelihoods, double livelihood patterns and spatial engineering (migration). Form of livelihood strategies that are conducted are affected by the livelihood utilization of hodge household. Livelihoods consist of the utilization of human capital, natural capital, physical capital, financial capital and social capital.